Synthesis of HTMS-HTES Hydrophobic Coating for Cotton and Polyester Fabrics via Sol-Gel Method - Nurul Hidayah, Abu Bakar; Wan Norfazilah, Wan Ismail (Malaysian Institute of Chemistry, 2024)
Hydrophobic coatings, inspired by the lotus effect, are favoured for repelling water and addressing challenges such as self-cleaning, oil/water separation, anti-icing, and stain resistance. Key requirements include nanoscale roughness and low surface energy materials. However, fluorinated chemicals in these coatings raise environmental concerns, prompting a demand for water-based alternatives. Producing water-based hydrophobic coatings poses challenges related to synthesising stable dispersions of low surface energy materials and identifying water-soluble adhesives. This study focuses on developing water-based hydrophobic coatings for cotton and polyester textiles using hexyltrimethoxysilane (HTMS) and hexyltriethoxysilane (HTES) via a sol-gel method. Hydrophobic properties were assessed through water contact angle (WCA) measurements and wettability observations. Fourier transform infrared spectroscopy (FTIR) analysed functional groups while scanning electron microscopy-energy dispersive X-ray analysis (SEM-EDX) examined surface morphology and elemental composition. Results showed favourable hydrophobic properties with HTMS-HTES coatings, as water droplets formed spherical shapes without penetrating fabric surfaces. WCA values reached 135.41° for cotton and 132.28° for polyester fabric at a 1:0.6 HTMS:HTES molar ratio, indicating enhanced hydrophobicity. FTIR confirmed siloxane Si-O-Si bond formation, and SEM-EDX indicated good adhesion, promising water-repellent textiles for various industries.